Inhibition of Nuclear Nox4 Activity by Plumbagin: Effect on Proliferative Capacity in Human Amniotic Stem Cells. (29th December 2013) - Guida, Marianna; Maraldi, Tullia; Resca, Elisa; Beretti, Francesca; Zavatti, Manuela; Bertoni, Laura; La Sala, Giovanni B.; De Pol, Anto
Abstract : Human amniotic fluid stem cells (AFSC) with multilineage differentiation potential are novel source for cell therapy. However, in vitro expansion leads to senescence affecting differentiation and proliferative capacities. Reactive oxygen species (ROS) have been involved in the regulation of stem cell pluripotency, proliferation, and differentiation. Redox-regulated signal transduction is coordinated by spatially controlled production of ROS within subcellular compartments. NAD(P)H oxidase family, in particular Nox4, has been known to produce ROS in the nucleus; however, the mechanisms and the meaning of this function remain largely unknown. In the present study, we show that Nox4 nuclear expression (nNox4) increases during culture passages up to cell cycle arrest and the serum starvation causes the same effect. With the decrease of Nox4 activity, obtained with plumbagin, a decline of nuclear ROS production and of DNA damage occurs. Moreover, plumbagin exposure reduces the binding between nNox4 and nucleoskeleton components, as Matrin 3. The same effect was observed also for the binding with phospho-ERK, although nuclear ERK and P-ERK are unchanged. Taken together, we suggest that nNox4 regulation may have important pathophysiologic effects in stem cell proliferation through modulation of nuclear signaling and DNA damage.